Upaya Peningkatan Pengetahuan Tentang Nutrisi Usia Prasekolah Pada Ibu Dengan Anak Status Gizi Kurang - Rohudyah Febri Hantari, Anisa; , Irdawati, S.Kep.,Ns.,M.Si.,Med (2017)
Background: The main problem in the structure of the world population is malnourished one. According to data from the World Health Organization (WHO, 2008), there are approximately 3.1 million children worldwide who die from malnutrition every day. Average -rata those under 5 years of age. Toddler age is an age-prone, due to growth in this period will determine the physical and mental development later. Intake of nutritious food is essential for the growth of brain cells and the physical. In this golden period, the growth of brain cells develop until the age of 3-4 years. In the development of the child, the mother is very dominant role to nurture and educate children to grow and develop into a qualified child. Eat at preschool parenting associated with eating habits that have been invested since the beginning of human growth. Objective: to describe efforts to increase knowledge about nutrition in preschool Mother An. N with malnutrition which include assessment,diagnose, intervention, implementation, and evaluation of nursing. Methods: Descriptive study approach. Result: after nursing for 1 x 20 minutes is obtained, Ms. An. N increased knowledge about nutrition for preschoolers.